PENDIDIKAN INKLUSI DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Putri, Suci Ananda; Putra, M. Jaya Adi; Hermita, Neni (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2019)
The background of this research is that researchers found several problems regarding the implementation of inclusive education, especially in terms of the process of learning inclusion in elementary schools. The study aims to describe how the inclusive learning process in one of the primary schools administering inclusive education in Pekanbaru. The inclusion learning process is seen from the application of indicators, there are three indicators The inclusion learning process studied in this study are: 1) Inclusion Learning Planning, 2) Inclusion Learning Implementation, 3) Evaluation and Follow-Up Inclusion Learning. The type of research used is qualitative research with descriptive methods, the instruments in this study are observation, interviews and documentation. Based on the results of the study it was found that: (1) In planning learning the classroom teacher first understood the characteristics of students in general, especially the characteristics of students with Special Needs, and learning planning contained in the same Learning Process Plan, both for regular students and students with Special Needs (2) The implementation of learning is carried out as planned in the Learning Process Plan . The teacher conducts conditioning by preparing students physically and psychologically. The use of models, methods, learning media is equated between regular and students with Special Needs, (3) In evaluation and follow-up, the teacher conducts a daily evaluation of each finished material and plans follow up activities with special companion teachers in the form of enrichment carried out in special guidance. In special guidance students were given enrichment material with the drill method plus media assistance in the form of concrete teaching aids to strengthen the understanding of students with Special Needs in a learning concept.